"Appraising and exploring organisations/ edited by Tyson, S. and ...[et al]" - S. Tyson (ed.) (London, 1988)
The first comprehensive and up-to-date description of the functions and performance of organizational surveys from a wide range of European experts in the field.
Keywords: Organisation-Research